2007
DOI: 10.1074/jbc.m701876200
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio vulnificus IlpA-induced Cytokine Production Is Mediated by Toll-like Receptor 2

Abstract: Vibrio vulnificus is a pathogenic bacterium causing primary septicemia, which follows a classical septic shock pathway, including an overwhelming inflammatory cytokine response. In this study, we identified a putative lipoprotein of V. vulnificus, encoded by the ilpA gene, as one of the surface proteins that specifically reacted with the antibodies raised against outer membrane proteins of V. vulnificus. Using a mutant V. vulnificus in which its ilpA gene was knocked out, we found that IlpA is important in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…In agreement with the pattern of DUSP1 activation, the Mapk14 gene (or p38α) was up-regulated by the Bt2-SerE strain, but down-regulated by the selected Bt1-RtxA1 1 strain. In contrast, mice infected with the Bt1-RtxA1 1 -strain developed a typical immune response against an extracellular pathogen: most of the CKS genes were down-regulated in these mice while genes known to have a beneficial role during extracellular bacterial infections ( Il6, Tnf or Lcn2 ) were clearly up-regulated (Shin et al, 2002; Berger et al, 2006; Goo et al, 2007; Chuang et al, 2010). Finally, we also found that the Bt1-RtxA1 1 strain induced high levels of the CCs Ccl3 and Cxcl1 .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the pattern of DUSP1 activation, the Mapk14 gene (or p38α) was up-regulated by the Bt2-SerE strain, but down-regulated by the selected Bt1-RtxA1 1 strain. In contrast, mice infected with the Bt1-RtxA1 1 -strain developed a typical immune response against an extracellular pathogen: most of the CKS genes were down-regulated in these mice while genes known to have a beneficial role during extracellular bacterial infections ( Il6, Tnf or Lcn2 ) were clearly up-regulated (Shin et al, 2002; Berger et al, 2006; Goo et al, 2007; Chuang et al, 2010). Finally, we also found that the Bt1-RtxA1 1 strain induced high levels of the CCs Ccl3 and Cxcl1 .…”
Section: Discussionmentioning
confidence: 99%
“…Cells were pre-incubated with anti-mouse TLR2 monoclonal antibody (Clone: T2.5, BioLegend), anti-human TLR2 monoclonal antibody (Clone: TL2.1, BioLegend) or its isotype control IgG (BioLegend). These antibodies are useful for blocking studies and have been reported to block TLR2-specific cell activation in vitro and in vivo 3941 .…”
Section: Methodsmentioning
confidence: 99%
“…It is able to accomplish this due to its innate virulence factors/determinants which enhance its pathogenicity, conferring the ability to survive in the human body (Jones and Oliver, 2009). Severe mechanisms contribute in attachment and invasion of a host, which including pili, OmpU , and IlpA membrane proteins and flagella (Jung et al, 2005; Goo et al, 2006, 2007; Jones and Oliver, 2009). V. vulnificus are also able to utilize Neu5Ac as a nutrient during infection in humans and survive in highly acidic environments by breaking down amino acids to amines and CO 2 (Jeong et al, 2009; Jones and Oliver, 2009).…”
Section: Characteristic Of Vibrio Vulnificusmentioning
confidence: 99%